TOXICITY TEST OF SMALL WHITE GINGER EXTRACT ON BHK-21 FIBROBLAST CELLS IN VITRO - Robiansyah Robiansyah; Debby Saputera; Rahmad Arifin (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Denture stomatitis is inflammation of the oral mucosa which supporting the denture that caused by Candida albicans. Candida albicans contamination can be prevented by immersing dentures into denture cleanser solution. One of the alternative ingredients that can be used as denture cleanser is small white ginger rhizome (Zingiber officinale var. Amarum). Objective: This study aimed to analyze whether small white ginger extract (Zingiber officinale var. Amarum) was toxic to BHK-21 fibroblast cells using the MTT assay method. Method: This study was conducted in 7 groups. Five groups consisted of extracts of 30%, 40%, 50%, 60%, 70% and 2 control groups comprised of media control and cell control. Absorbance was read using ELISA reader and cell viability was calculated. Results: The percentage of living cells of all groups of small white ginger extract treatment was 100%. The parametric analysis of One Way Annova showed p = 0.498 (p> 0.05) Conclusion: Small white ginger extract (Zingiber officinale var. Amarum) is not toxic to BHK-21 fibroblast cells using the MTT Assay method because cell viability of all concentration groups is  ≥ 60%.